Saharan Dust Deposition Effects on the Microbial Food Web in the Eastern Mediterranean: A Study Based on a Mesocosm Experiment - Pitta, Paraskevi; Kanakidou, Maria; Mihalopoulos, Nikolaos; Christodoulaki, Sylvia; Dimitriou, Panagiotis D.; Frangoulis, Constantin; Giannakourou, Antonia; Kagiorgi, Margarita; Lagaria, Anna; Nikolaou, Panagiota; Papageorgiou, Nafsika; Psarra, Stella; et al. (Frontiers in Marine Science, 2017)
The effect of episodicity of Saharan dust deposition on the pelagic microbial food web was studied in the oligotrophic Eastern Mediterranean by means of a mesocosm experiment in May 2014. Two different treatments in triplicates (addition of natural Saharan dust in a single-strong pulse or in three smaller consecutive doses of the same total quantity), and three unamended controls were employed; chemical and biological parameters were measured during a 10-day experiment. Temporal changes in primary (PP) and bacterial (BP) production, chlorophyll a (Chla) concentration and heterotrophic bacteria, Synechococcus and mesozooplankton abundance were studied. The results suggested that the auto- and hetero-trophic components of the food web (at least the prokaryotes) were enhanced by the dust addition (and by the nitrogen and phosphorus added through dust). Furthermore, a 1-day delay was observed for PP, BP and Chla increases when dust was added in three daily doses; however, the maximal values attained were similar in the two treatments. Although the effect was evident in the first osmotrophic level (phytoplankton and bacteria), it was lost further up the food web, masked under the impact of grazing exerted by predators such as heterotrophic flagellates, ciliates and dinoflagellates. This was partly proved by two dilution experiments. This study demonstrates the important role of atmospheric deposition and protist grazing when evaluating the effect on oligotrophic systems characterised by increased numbers of trophic levels.